PENGARUH MEDIA CANVA TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS V SD - ihsan misbah khudin, muhammad; Lita Sandra Dewi, Anggra; Erdiana, Lita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of the use of Canva digital media on the Indonesian learning outcomes of grade V students of SDIT EL-HAQ, especially in poster making materials. The background of this research is based on the low interest and learning outcomes of students due to learning methods that tend to be monotonous. The research uses a quantitative method with a quasi-experiment design in the form of a nonequivalent control group design, involving two classes, namely the experimental class (using canva) and the control class (without canva), each with a total of 20 students. Data collection techniques include expert validation, learning outcome tests (pretest and posttest), as well as validity, reliability, normality, homogeneity, and t-test tests.The results showed that Canva media obtained a validation score of 91% with the category of very feasible and the reliability of the instrument of α = 0.839. The normality and homogeneity test confirms that the data is distributed normally and homogeneously. The results of the t-test showed a significant difference between the experimental and control classes, with the average score of the experimental class increasing from 57.61 (pretest) to 85.87 (posttest). It can be concluded that the use of canva has a positive and significant influence on improving student learning outcomes, as well as being able to increase their interest and creativity in learning Indonesian.